A rapid spectrophotometric method to resolve ternary mixtures of propyphenazone, caffeine, and acetaminophen in tablets - Özgür, MÜ; Alpdogan, G; Asçi, B (SPRINGER-VERLAG WIEN, 2002)
A simple and rapid derivative spectrophotometric assay procedure is described for the analysis of caffeine (1), acetaminophen (2), and propyphenazone (3) in tablet formulations. The concentration range of application is 5.0-25.0 mug.cm(-3) for 2 and 3 and 1.0-5.0 mug.cm(-3) for 1. The method involves the extraction of the drugs from tablets with 0.1 NH2SO4, filtration, appropriate dilution, and measurement of the fourth derivative absorbance values at zero crossing wavelengths of 230.0, 263.2. and 256.6 nm for 1, 2, and 3. As a reference method, a reversed phase HPLC procedure was developed. Commercially available tablets were analyzed; statistical comparison of the results with those obtained from the reference method showed good agreement. The derivative spectrophotometric method has the advantage of being simple, rapid, inexpensive, and easy to perform.
Keywords: derivative spectrophotometry; pharmaceuticals analysis; simultaneous determination of drugs; SUNSET YELLOW; RATIO SPECTRA; CALIBRATION; Chemistry